Separation of Zr and Hf from strong hydrochloric acid solution by solvent extraction with TEHA - Banda, Raju; Lee, Hwa Young; Lee, Man Seung (SPRINGER, 2013)
In order to separate Zr(IV) and Hf(IV) from chloride solutions, TEHA (tri 2-ethyl hexyl amine) was used as an extractant. The aqueous phase consisted of 200 ppm of Zr and Hf in strong HCl solution. In our solvent extraction system, the extractability of the constituents by TEHA was found to be in the following order, HCl > Zr(IV) > Hf(IV). The highest separation factor between the two metals was obtained from 8 M HCl solution. Based on the selectivity towards Zr over Hf with TEHA, McCabe-Thiele plot was constructed and batch simulation of counter-current extraction studies has been conducted. Scrubbing results from the loaded TEHA showed that Hf was selectively scrubbed over Zr by strong HCl solution (9 M). Complete stripping of Zr was possible from the organic phase with distilled water after scrubbing of Hf. The extraction behavior of Zr and Hf by TEHA was compared with that by TiOA and TOA. Our results can be utilized in developing a solvent extraction process to separate Zr and Hf from concentrated chloride solutions by using TEHA.
Keywords: GEOLOGICAL-MATERIALS; HAFNIUM SEPARATION; ION-EXCHANGERS; ZIRCONIUM; CHROMATOGRAPHY; MEDIA; ALIQUAT-336; MIXTURES; CHLORIDE; AMINES